THE MODEL OF THE DIGITAL FILTER KALMAN-BUCY (Новітні інформаційні системи та технології, 2014)
New automatic methods of TMN, TINA types make it possible to complete necessary changes and updating of network elements modes and networks structure, to perform network resources remapping according to the rerouting control in telecommunication systems. Provided changes offer random probabilities which transiency emerges at the lowest operation hours. It is obviously that nonstationarity generates a need for the indicated updating and network restructuring realization. There is not necessary to update the network during the hypothesized stationary operation in the condition if the system operates without failings.